Smart Arm-Autonomous Low-Cost Device for Smart Agriculture - H, Jayalaxmi; K, Shashikumar; H, Shridhar (Journal of Advanced Research in Signal Processing and Applications, 2022)
Agriculture is quickly changing technology to ensure reliability, reduce natural resources usage of the cost and keep up with the increasing demand for food. This is a born for large scale industries and personal agriculture like as it reduces the cost of manual labor for industries. Agriculture autonomous using Smart arm is used to condense the maintenance load with automaton of seed sowing, crop harvesting, pesticide spryer and areca nut or coconut plucking in trees. It is use in more reliable, cost effective and efficient agriculture systems. This paper presents a simplified approach to future smart arm Autonomous Agriculture. The implementation of modular farming automation system has been discussed. There is a plucking arm which provides interface of attaching new modules to the existing implementation. Low cost Zigbee technology allows an electronic device to exchange data wirelessly, including monitoring and controlling. How to cite this article: Jayalaxmi H, Shashikumar K, Shridhar H. Smartarm-Autonomous Low-Cost Device for Smart Agriculture. J Adv Res Sig Proc Appl 2021; 3(1): 1-3.